IMPLEMENTATION OF VALUE CREATION IN PUBLIC TRANSPORT (CASE STUDY: PT. KAI CUSTOMER SATISFACTION) - Indramawan, Andi; Johnshon, Mikael; Malkamah, Siti (FSTPT Indonesia, 2015)
PT. KAI as the train operator in Indonesia need to provide good service quality that will result in customer satisfaction. To evaluate service quality need to be known customer expectation and customer perception toward services offered. From Importance-Performance Analysis, shown that punctuality, easiness to mode change and waiting room are attributes that belong to performance shortfall, that means those attributes need to get priority in improvement. Then regression analysis was conducted to know how quality attibutes influence the satisfaction. The result show that, there are two component factor that are main services and additional services. All of three attrtibutes that obtained from IPA analysis belong to main services that has significant influences to customer satisfaction. Related with value creation dimension, PT. KAI need to improve services quality in customer experience. Customer who has good experiences toward service offered can increase level of satisfaction and create positive emotional bonds.